Persepsi Masyarakat Terhadap Makanan Berbahan Dasar Singkong yang diolah Secara Tradisional dan Kekinian - Hidayat, Candra; Abduh, Mohammad Syaltut (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
Indonesia ranks fifth in the world’s cassava production with a total production of 19,436,640 tons. Cassava is a staple food for Indonesians and growns in almost all parts of Indonesia. However nowadays, the existence of cassava as a staple is replaced by other types of food, especially with the arrival of fast food from abroad. This study aims to determine the extent and how to use cassava as the main raw material for traditional food in the community. Because if it is ignored one day cassava would no longer be a food commodity. The research method used were interviews and questionnaires. Interviews were conducted with ten respondents who were considered randomly representative (random sampling). As results of this study, it turned out that some people still faithfully consume cassava but not as a staple but as a side dish. Then it was observed that packaging and product innovation were also needed in this regard.